Chinese Working-Class Lives Getting By in Taiwan - Gates, Hill (Cornell University Press, 1988)
Taiwan's working class has been shaped by Chinese tradition, by colonialism, and by rapid industrialization. This book defines that class, explores that history, and presents with sensitive honesty the life experiences of some of its women and men. Hill Gates first provides a solid and informative introduction to Taiwan's history, showing how mainland China, Japan, the convulsions of twentieth-century wars, and the East Asian economic expansion interacted in forming Taiwanese urban life. She introduces nine individuals from Taiwan's three major ethnic groups to tell the stories of their lives in their own words. The narrators include a fortuneteller, a woman laborer, and a retired air force mechanic. A former spirit medium and a janitor are among the others who speak.